Einflussfaktoren auf die Rehospitalisierungsrate bei Alkoholabhängigkeit: Originalien - Koopmann, Anne; Hoffmann, Sabine; Riegler, Alisa; Cordes, Jaspar; Kiefer, Falk (Der Nervenarzt, 2024)
Background According to data from the Federal Statistical Office, the diagnosis of alcohol use disorder (AUD) (F 10) is the second most common main diagnosis for hospital treatment. Those affected by this disorder are often repeatedly hospitalized at short intervals due to relapses; however, little is known about the factors that influence readmission rates after initial treatment. Aim of the study The aim of this retrospective analysis is to analyze the effects of treatment type (qualified withdrawal treatment (QE) versus physical detoxification) and discharge mode on the probability of readmission in alcohol-dependent patients after inpatient treatment. Material and methods Data from 981 male and female alcohol-dependent patients who completed either qualified withdrawal treatment (QE) (68% men; mean age 47.6 years) or inpatient detoxification (74% men; mean age 48.0 years) were analyzed. Predictors of regular discharge were determined separately for both types of treatment using stepwise logistic regression. Results Patients who had completed a qualified withdrawal treatment were significantly more likely to be regularly discharged. Regular completion of the qualified withdrawal treatment (QE) led to a relative reduction in the readmission rate of 25.64% within 1 year compared to a physical detoxification. Conclusion In order to prevent readmission and chronic courses of alcohol use disorder (AUD), qualified withdrawal treatment should always be recommended to affected patients instead of physical detoxification. Aktuelle Daten des Statistischen Bundesamtes für das Jahr 2022 zeigen, dass die Diagnose „Psychische und Verhaltensstörungen durch Alkohol (F 10.X)“ die zweithäufigste Hauptdiagnose bei Krankenhausbehandlungen darstellt [13]. Im Gesundheitssystem entstehen durch dieses Erkrankungsbild und seine somatischen und psychischen Folgeerkrankungen jährlich ca. 10Mrd. € direkte Kosten [13]. Dieser Sachverhalt wird dadurch kontrastiert, dass die Krankenkassen die qualifizierte Entzugsbehandlung (QE) als leitliniengerechte Goldstandardtherapie [4] wiederholt infrage stellen [10].
Online veröffentlicht: 16. September 2024
Gesehen am 21.01.2025